High-strength energy storage floor tile as well as preparation method and application thereof
By adopting cement-based electrolyte and mesh electrodes with directionally arranged hole structures in the energy storage floor tiles, combined with the ultra-high performance concrete shell, the problem of low ionic conductivity and stability of existing energy storage floor tiles is solved, and high-efficiency energy storage and safe high-strength energy storage floor tiles are achieved.
Patent Information
- Application Number
- CN202411679203.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The ionic conductivity and stability of existing energy storage floor tiles are not high, resulting in insufficient energy storage and safety.
Cement-based electrolyte with a directional arrangement of hole structure is used as an energy storage sandwich, and mesh electrodes are assembled on both sides of it, combined with ultra-high performance concrete as a high-strength shell, and the ionic conductivity and stability of floor tiles are improved through refrigerated casting and electrochemical energy storage technology.
High-strength energy storage floor tiles with high ionic conductivity and high stability have been achieved, which enhances their performance in energy storage and safety, and has high mechanical properties, which are suitable for the construction field.
Smart Images

Figure CN119686507A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a high-strength energy storage floor tile and a preparation method and application thereof. Background Art
[0002] With the development of modern construction technology, the functional performance requirements of building materials are increasing. Although traditional floor tiles perform well in terms of strength and durability, their functions are single and there is great room for improvement. With the continuous increase in energy storage needs, the development of low-carbon building materials with energy storage functions has gradually become a research hotspot. However, the existing energy storage floor tile technology has not yet been commercialized, and the research on energy storage materials based on cement or concrete is still in its infancy and faces many technical challenges. How to give the floor tiles an electrochemical storage function while ensuring their mechanical properties is an important trend in the low-carbon development of building materials. Ionic conductivity is a key indicator of energy storage floor tiles. At present, there are methods to improve ionic conductivity, such as adding ion conductive additives, introducing polymer electrolytes, adding metal oxides or nanomaterials, and introducing liquid electrolytes. Adding ion conductive additives may cause corrosion of electrode materials and weaken the structural stability of the materials. Polymer electrolytes are easy to decompose and age, which will affect the long-term stability of energy storage floor tiles, and uneven distribution will significantly reduce their overall performance. Adding metal oxides or nanomaterials may face a significant increase in costs and may have problems with uneven distribution. The use of liquid electrolytes faces the risk of leakage, which affects the safety of energy storage floor tiles. Therefore, the development of high-strength energy storage floor tiles with high ionic conductivity and high stability has become a current research hotspot. Summary of the invention
[0003] The purpose of the present invention is to provide a high-strength energy storage floor tile and a preparation method and application thereof, so as to solve the problem of low ion conductivity and stability of energy storage floor tiles in the prior art.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] The invention provides a high-strength energy storage floor tile, comprising an energy storage core and a high-strength shell covering the core.
[0006] Preferably, the energy storage sandwich comprises a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell.
[0007] Preferably, the cement-based electrolyte has a directional pore structure with a pore size of 10-20 μm and a porosity of 25-40%.
[0008] Preferably, the positive electrode and the negative electrode are mesh electrodes.
[0009] Preferably, the positive electrode and the negative electrode are respectively arranged at two ends of the directionally arranged pore structure.
[0010] Preferably, the energy storage core has a length×width of (250-260)×(250-260) mm and a vertical height of 5-7 mm.
[0011] Further preferably, the energy storage core has a length×width of 260×260 mm and a vertical height of 7 mm.
[0012] Preferably, the length×width of the high-strength energy storage floor tile is (290-300)×(290-300) mm, and the vertical height is 13-15 mm.
[0013] Further preferably, the length×width of the high-strength energy storage floor tile is 300×300 mm, and the vertical height is 15 mm.
[0014] Preferably, the pores of the directionally arranged pore structure are oriented in the same direction as the vertical direction of the cement-based electrolyte, and the positive electrode and the negative electrode are respectively arranged on both sides of the vertical direction of the cement-based electrolyte.
[0015] Preferably, the cement-based electrolyte comprises the following components in parts by mass:
[0016]
[0017] Further preferably, the cement-based electrolyte comprises the following components in parts by mass:
[0018]
[0019] Preferably, the ultra-high performance concrete-based shell comprises the following components in parts by mass:
[0020]
[0021]
[0022] Further preferably, the ultra-high performance concrete-based shell comprises the following components in parts by mass:
[0023]
[0024] Preferably, the cementitious material is selected from any one or more of Portland cement, fly ash and silica fume.
[0025] Preferably, the water reducer is a polycarboxylate water reducer.
[0026] Preferably, the modifier is polyacrylamide.
[0027] Preferably, the early strength agent is selected from any one or more of gypsum and water glass.
[0028] Preferably, the filler is selected from any one or more of silica fume, quartz sand and quartz powder.
[0029] In a second aspect, the present invention further provides a method for preparing the above-mentioned high-strength energy storage floor tiles, comprising the following steps:
[0030] S1: Mix the cementitious material, water reducing agent, early strength agent and water, then add the modifier, and mix them to obtain slurry A;
[0031] S2: Pour slurry A into the energy storage sandwich mold and let it stand;
[0032] S3: placing the energy storage sandwich mold filled with slurry A on an ultra-low temperature medium for freeze casting to obtain a solidified energy storage sandwich material B;
[0033] S4: thawing the solidified energy storage sandwich material B to obtain energy storage sandwich material C, and then placing the energy storage sandwich material C in a cement curing box for curing to obtain energy storage sandwich material D with a directional pore structure;
[0034] S5: immersing the energy storage sandwich material D having a directional pore structure into an electrolyte solution to obtain an energy storage sandwich material E having a directional pore structure, namely a cement-based electrolyte;
[0035] S6: Immerse the electrode material in a liquid nitrogen solution for cold shrinkage, and then quickly splice the electrode with the energy storage sandwich material E having a directional pore structure to obtain an assembled energy storage sandwich F;
[0036] S7: Stir the silicate cement and filler evenly according to the proportion, add the mixed solution of water reducer and water, and stir evenly again to obtain slurry G;
[0037] S8: Place the energy storage sandwich into a high-strength shell mold, pour in slurry G, make the slurry G surround the energy storage sandwich, and after curing in a standard concrete curing box for 20-32 days, obtain the high-strength energy storage floor tile.
[0038] Preferably, in step S1, the cementitious material, water reducing agent, early strength agent and water are stirred and mixed at a speed of 55-65 r / min and a stirring time of 60-80 s.
[0039] Preferably, in step S1, the speed of stirring and mixing after adding the modifier is 120-140 r / min, and the stirring time is 50-70 s.
[0040] Preferably, in step S2, the energy storage sandwich mold includes a high thermal conductivity platform, a grid base arranged on the high thermal conductivity platform, a low thermal conductivity frame arranged around the grid base, and a low thermal conductivity grid cover plate arranged on the low thermal conductivity frame, and the energy storage sandwich mold has only the high thermal conductivity platform in contact with the ultra-low temperature medium.
[0041] Preferably, in step S2, slurry A is poured into an energy storage sandwich mold and covered with a low thermal conductivity grid cover plate and then allowed to stand for 8 to 15 seconds, more preferably 10 seconds.
[0042] Preferably, in step S3, the freezing casting time is 30-50 minutes, and the freezing casting time is closely related to the height of the ultra-low temperature medium and the energy storage sandwich material B.
[0043] Further preferably, in step S3, the ultra-low temperature medium is liquid nitrogen, and the temperature of the liquid nitrogen is -190--180°C.
[0044] More preferably, in step S3, when the vertical height of the energy storage sandwich material B is 7 mm, the freezing casting is required for 30 minutes, and when the vertical height of the energy storage sandwich material B is 20 mm, the freezing casting is required for 50 minutes.
[0045] Preferably, in step S4, the thawing refers to placing the energy storage sandwich material B in a constant temperature environment of 0-4°C for curing.
[0046] Further preferably, when the vertical height of the energy storage sandwich material B is 5 mm, curing is required for 18 hours.
[0047] Further preferably, when the vertical height of the energy storage sandwich material B is 7 mm, curing is required for 20 hours.
[0048] Preferably, in step S5, the electrolyte solution is a zinc sulfate solution, and the concentration of the zinc sulfate solution is 1-2M, more preferably 2M.
[0049] Preferably, in step S5, the immersion time is related to the vertical height of the energy storage sandwich material D. When the vertical height of the energy storage sandwich material D is 5 mm, it needs to be immersed for 24 hours. When the vertical height of the energy storage sandwich material D is 7 mm, it needs to be immersed for 48 hours. After taking it out, let it stand for 3 hours, and then wipe off the surface liquid.
[0050] Preferably, in step S6, the electrode material is a mesh electrode, the electrode material includes a positive electrode and a negative electrode, the positive electrode is a vanadium oxide mesh electrode, the negative electrode is a zinc mesh electrode, and the electrode material is immersed in a liquid nitrogen solution for shrinkage for 20-40 seconds.
[0051] Preferably, step S8 comprises the following steps:
[0052] S8.1: Pour 35-50wt% of slurry G into the high-strength shell mold, and the height of the poured slurry G needs to be flush with the base in the high-strength shell mold;
[0053] S8.2: Place the assembled energy storage sandwich F on the base in the high-strength shell mold, pour in the remaining slurry G, so that the slurry G surrounds the energy storage sandwich and cure it in a standard concrete curing box for 20-32 days to obtain the high-strength energy storage floor tile.
[0054] Preferably, in step S8.1, after pouring the 35-50wt% slurry G, the high-strength shell mold needs to be placed on a concrete vibration table and vibrated for 20-40s.
[0055] Preferably, in step S8.2, after pouring the remaining slurry G, the high-strength shell mold needs to be placed on a concrete vibration table and vibrated for 40-60 seconds.
[0056] Preferably, the entire process of step S8 takes no longer than 5 minutes to complete.
[0057] In a third aspect, the present invention also provides an application of the above-mentioned high-strength energy storage floor tiles in the field of architectural decoration.
[0058] The high-strength energy storage floor tile designed by the present invention has dual functions, which are not only reflected in its strength, wear resistance and aesthetics as a floor material, but also in its energy storage characteristics. This floor tile can be combined with landscape design and used as a floor paving material for courtyards, trails, squares, etc., which is both practical and beautiful. It can not only store solar energy, but also provide electricity for nighttime landscape lighting, thereby effectively storing electrical energy.
[0059] The battery built into the high-strength energy storage floor tile designed by the present invention stores and releases energy through the exchange of charges. During the discharge process, zinc loses electrons at the negative electrode, oxidizes to Zn2+ and enters the electrolyte; at the same time, vanadium oxide accepts electrons at the positive electrode to form V3+. During the charging process, zinc ions return to the negative electrode and accept electrons, reducing to zinc metal; V3+ loses electrons at the positive electrode and recovers to vanadium oxide. This reaction cycle allows floor tiles to provide traditional functions while also serving as a sustainable energy solution.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] (1) The present invention prepares a high-strength energy storage floor tile by assembling a mesh electrode on the surface of a cement-based electrolyte with a directional pore structure as an energy storage sandwich and selecting ultra-high performance concrete as a high-strength outer shell. The high-strength energy storage floor tile has high ionic conductivity and high stability.
[0062] (2) The present invention constructs directional channels inside high-strength concrete through freeze casting. This directional channel design not only effectively improves the migration speed of ions, but also ensures that the overall performance of the material will not be damaged by the introduction of pores. The use of a special mesh mold reduces the interface impedance between the cement-based electrolyte and the electrode.
[0063] (3) The high-strength energy storage floor tiles of the present invention, because they use an ultra-high performance concrete matrix as a high-strength outer shell, can not only prevent electrolyte leakage, but also further improve the toughness and bearing capacity of the floor tiles, so that they have higher mechanical properties. They can be used in the construction field, realizing the integration of decoration, energy storage and structural performance, and greatly improving the functional level of traditional building materials.
[0064] (4) The high-strength energy storage floor tiles of the present invention use solid waste, such as fly ash and silica fume, to achieve high strength and energy storage functions while disposing of waste, thus promoting the low-carbon development of traditional building materials and providing new solutions for future smart buildings and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 It is a schematic diagram of the overall structure of the energy storage sandwich mold of the high-strength energy storage floor tile of the present invention;
[0066] Figure 2 It is a structural schematic diagram of a low thermal conductivity grid cover plate of an energy storage sandwich mold of a high-strength energy storage floor tile of the present invention;
[0067] Figure 3 It is a schematic diagram of the internal structure of the energy storage sandwich mold of the high-strength energy storage floor tile of the present invention;
[0068] Figure 4 It is a schematic diagram of energy storage sandwich assembly of the high-strength energy storage floor tile of the present invention;
[0069] Figure 5 This is a schematic diagram of a high-strength shell mold for the high-strength energy storage floor tile of the present invention;
[0070] Figure 6 A schematic diagram (front view) of the dimensions of the high-strength energy storage floor tile of Example 1 of the present invention (in the figure, h=15mm, m=4mm, n=7mm);
[0071] Figure 7 This is a schematic diagram (top view) of the dimensions of the high-strength energy storage floor tile of Example 1 of the present invention (in the figure, a=300mm, b=280mm, c=20mm);
[0072] In the figure: 1-high thermal conductivity platform; 2-grid base; 3-low thermal conductivity frame; 4-low thermal conductivity grid cover; 5-energy storage sandwich mold; 6-base; 7-high strength shell mold; H-zinc mesh electrode; I-vanadium oxide mesh electrode; E-cement-based electrolyte; F-energy storage sandwich; J-high strength shell. DETAILED DESCRIPTION
[0073] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0074] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0075] Example 1
[0076] A high-strength energy storage floor tile comprises an energy storage core and a high-strength outer shell covering the core.
[0077] like Figure 4 As shown, the energy storage sandwich includes a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell.
[0078] The cement-based electrolyte comprises the following components in parts by mass:
[0079] 70 parts of cementitious materials;
[0080]
[0081] The ultra-high performance concrete shell includes the following components in parts by mass:
[0082]
[0083] In this embodiment, the positive electrode is a vanadium oxide mesh electrode, and the negative electrode is a zinc mesh electrode.
[0084] In this embodiment, the cementitious material includes the following components by mass: 80% silicate cement, 10% fly ash, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically a high early strength polycarboxylic acid water reducer; the modifier is polyacrylamide (weight average molecular weight is 10 million Daltons); the early strength agent includes the following components by mass: 50% gypsum, 50% water glass, wherein the modulus of water glass is 2.5. The filler includes the following components by mass: 20% silica fume, 72% quartz sand with a particle size of 0.4-1 mm, and 8% quartz powder with a particle size of 5-100 μm.
[0085] The preparation process of the high-strength energy storage floor tile is as follows: first, 70 parts of cementitious material, 0.18 parts of water reducing agent, 5.25 parts of early strength agent and 35 parts of water are placed in a stirring pot and mixed evenly, and then 0.11 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into an energy storage sandwich mold 5 with a high thermal conductivity platform 1 at the bottom (structure as shown in FIG. Figure 1-3 As shown), after standing for 10 seconds, transfer to an ultra-low temperature medium for freeze casting, freeze for 24 hours until the block is completely solidified, and obtain a solidified energy storage sandwich material B. The energy storage sandwich material B is slowly thawed in an environment of 0-4°C for 20 hours to obtain an energy storage sandwich material C, and the energy storage sandwich material C is placed in a cement standard curing box and cured for 28 days to obtain an energy storage sandwich material D with a directional pore structure. The energy storage sandwich material D with a directional pore structure is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain an energy storage sandwich material E with a directional pore structure, i.e., a cement-based electrolyte. The vanadium oxide mesh electrode and the zinc mesh electrode are immersed in liquid nitrogen and frozen for 30 seconds, and after being taken out, they are quickly spliced with the energy storage sandwich material E with a directional pore structure to obtain an assembled energy storage sandwich F.
[0086] 130 parts of Portland cement and 215 parts of filler were poured into a stirring pot and stirred at a speed of 130 r / min for 1 minute. 27 parts of water and 3.15 parts of water reducer were mixed and added to a stirrer and stirred at a speed of 60 r / min for 3 minutes to obtain slurry G. A portion of slurry G was poured into a high-strength shell mold 7 (such as Figure 5 As shown), make the slurry G flush with the base 6 in the high-strength shell mold 7, place the mold on a concrete vibration table and vibrate for 30 seconds, then put the assembled energy storage sandwich F into the base 6 of the high-strength shell mold 7, pour in the remaining slurry G, place the mold on a concrete vibration table and vibrate for 50 seconds, put it into a standard concrete curing box, and after 28 days, high-strength energy storage floor tiles are obtained. The size of the prepared high-strength energy storage floor tiles is 300×300×15mm, and the size of the energy storage sandwich is 260×260×7mm. The size diagram is shown in Figure 6-7 shown.
[0087] Example 2
[0088] A high-strength energy storage floor tile comprises an energy storage core and a high-strength outer shell covering the core.
[0089] like Figure 4 As shown, the energy storage sandwich includes a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell.
[0090] The cement-based electrolyte comprises the following components in parts by mass:
[0091]
[0092] The ultra-high performance concrete shell includes the following components in parts by mass:
[0093]
[0094] In this embodiment, the positive electrode is a vanadium oxide mesh electrode, and the negative electrode is a zinc mesh electrode.
[0095] In this embodiment, the cementitious material includes the following components by mass: 80% silicate cement, 10% fly ash, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically a high early strength polycarboxylic acid water reducer; the modifier is polyacrylamide (weight average molecular weight is 10 million Daltons); the early strength agent includes the following components by mass: 50% gypsum, 50% water glass, wherein the modulus of water glass is 2.5. The filler includes the following components by mass: 20% silica fume, 72% quartz sand with a particle size of 0.4-1 mm, and 8% quartz powder with a particle size of 5-100 μm.
[0096] The preparation process of the high-strength energy storage floor tile is as follows: first, 70 parts of cementitious material, 0.18 parts of water reducing agent, 5.25 parts of early strength agent and 20 parts of water are placed in a stirring pot and mixed evenly, and then 0.11 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into an energy storage sandwich mold 5 with a high thermal conductivity platform 1 at the bottom (structure as shown in FIG. Figure 1-3 As shown), after standing for 10 seconds, transfer to an ultra-low temperature medium for freeze casting, freeze for 24 hours until the block is completely solidified, and obtain a solidified energy storage sandwich material B. The energy storage sandwich material B is slowly thawed in an environment of 0-4°C for 20 hours to obtain an energy storage sandwich material C, and the energy storage sandwich material C is placed in a cement standard curing box and cured for 28 days to obtain an energy storage sandwich material D with a directional pore structure. The energy storage sandwich material D with a directional pore structure is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain an energy storage sandwich material E with a directional pore structure, i.e., a cement-based electrolyte. The vanadium oxide mesh electrode and the zinc mesh electrode are immersed in liquid nitrogen and frozen for 30 seconds, and after being taken out, they are quickly spliced with the energy storage sandwich material E with a directional pore structure to obtain an assembled energy storage sandwich F.
[0097] 130 parts of Portland cement and 215 parts of filler were poured into a stirring pot and stirred at a speed of 130 r / min for 1 minute. 27 parts of water and 3.15 parts of water reducer were mixed and added to a stirrer and stirred at a speed of 60 r / min for 3 minutes to obtain slurry G. A portion of slurry G was poured into a high-strength shell mold 7 (such as Figure 5As shown), make the slurry G flush with the base 6 in the high-strength shell mold 7, place the mold on a concrete vibration table and vibrate for 30 seconds, then place the assembled energy storage sandwich F on the base 6 of the high-strength shell mold 7, pour in the remaining slurry G, place the mold on a concrete vibration table and vibrate for 50 seconds, put it into a standard concrete curing box, and after 28 days, high-strength energy storage floor tiles are obtained. The prepared high-strength energy storage floor tiles have a size of 300×300×15mm, and the size of the energy storage sandwich is 260×260×7mm.
[0098] Example 3
[0099] A high-strength energy storage floor tile comprises an energy storage core and a high-strength outer shell covering the core.
[0100] like Figure 4 As shown, the energy storage sandwich includes a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell.
[0101] The cement-based electrolyte comprises the following components in parts by mass:
[0102]
[0103] The ultra-high performance concrete shell includes the following components in parts by mass:
[0104]
[0105] In this embodiment, the positive electrode is a vanadium oxide mesh electrode, and the negative electrode is a zinc mesh electrode.
[0106] In this embodiment, the cementitious material includes the following components by mass: 80% silicate cement, 10% fly ash, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically a high early strength polycarboxylic acid water reducer; the modifier is polyacrylamide (weight average molecular weight is 10 million Daltons); the early strength agent includes the following components by mass: 50% gypsum, 50% water glass, wherein the modulus of water glass is 2.5. The filler includes the following components by mass: 20% silica fume, 72% quartz sand with a particle size of 0.4-1 mm, and 8% quartz powder with a particle size of 5-100 μm.
[0107] The preparation process of the high-strength energy storage floor tile is as follows: first, 70 parts of cementitious material, 0.18 parts of water reducing agent, 5.25 parts of early strength agent and 35 parts of water are placed in a stirring pot and mixed evenly, and then 0.11 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into an energy storage sandwich mold 5 with a high thermal conductivity platform 1 at the bottom (structure as shown in FIG. Figure 1-3As shown), after standing for 10 seconds, transfer to an ultra-low temperature medium for freeze casting, freeze for 24 hours until the block is completely solidified, and obtain a solidified energy storage sandwich material B. The energy storage sandwich material B is slowly thawed in an environment of 0-4°C for 20 hours to obtain an energy storage sandwich material C, and the energy storage sandwich material C is placed in a cement standard curing box and cured for 28 days to obtain an energy storage sandwich material D with a directional pore structure. The energy storage sandwich material D with a directional pore structure is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain an energy storage sandwich material E with a directional pore structure, i.e., a cement-based electrolyte. The vanadium oxide mesh electrode and the zinc mesh electrode are immersed in liquid nitrogen and frozen for 30 seconds, and after being taken out, they are quickly spliced with the energy storage sandwich material E with a directional pore structure to obtain an assembled energy storage sandwich F.
[0108] 130 parts of Portland cement and 215 parts of filler were poured into a stirring pot and stirred at a speed of 130 r / min for 1 minute. 50 parts of water and 3.15 parts of water reducer were mixed and added to a stirrer and stirred at a speed of 60 r / min for 3 minutes to obtain slurry G. A portion of slurry G was poured into a high-strength shell mold 7 (such as Figure 5 As shown), make the slurry G flush with the base 6 in the high-strength shell mold 7, place the mold on a concrete vibration table and vibrate for 30 seconds, then place the assembled energy storage sandwich F on the base 6 of the high-strength shell mold 7, pour in the remaining slurry G, place the mold on a concrete vibration table and vibrate for 50 seconds, put it into a standard concrete curing box, and after 28 days, high-strength energy storage floor tiles are obtained. The prepared high-strength energy storage floor tiles have a size of 300×300×15mm, and the size of the energy storage sandwich is 260×260×7mm.
[0109] Comparative Example 1
[0110] Energy storage floor tile
[0111] The cement-based electrolyte comprises the following components in parts by mass:
[0112]
[0113]
[0114] In this comparative example, the positive electrode is a vanadium oxide mesh electrode, and the negative electrode is a zinc mesh electrode.
[0115] In this comparative example, the cementitious material includes the following components in mass fractions: 80% silicate cement, 10% fly ash, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically a high early strength polycarboxylic acid water reducer; the modifier is polyacrylamide (weight average molecular weight is 10 million Daltons); the early strength agent includes the following components in mass fractions: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5. The filler includes the following components in mass fractions: 20% silica fume, 72% quartz sand with a particle size of 0.4-1 mm, and 8% quartz powder with a particle size of 5-100 μm.
[0116] The preparation process of the high-strength energy storage floor tile is as follows: first, 70 parts of cementitious material, 0.18 parts of water reducing agent, 5.25 parts of early strength agent and 35 parts of water are placed in a stirring pot and mixed evenly, and then 0.11 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into an energy storage sandwich mold 5 with a high thermal conductivity platform 1 at the bottom (structure as shown in FIG. Figure 1-3 As shown), after standing for 10 seconds, transfer to an ultra-low temperature medium for freeze casting, freeze for 24 hours until the block is completely solidified, and obtain solidified energy storage sandwich material B. The energy storage sandwich material B is placed in an environment of 0-4°C and slowly thawed for 20 hours to obtain energy storage sandwich material C, and the energy storage sandwich material C is placed in a cement standard curing box and cured for 28 days to obtain energy storage sandwich material D with a directional pore structure. The energy storage sandwich material D with a directional pore structure is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain energy storage sandwich material E with a directional pore structure, namely a cement-based electrolyte. The vanadium oxide mesh electrode and the zinc mesh electrode are immersed in liquid nitrogen and frozen for 30 seconds. After being taken out, they are quickly spliced with the energy storage sandwich material E with a directional pore structure to obtain energy storage floor tiles.
[0117] Comparative Example 2
[0118] A high-strength energy storage floor tile comprises an energy storage core and a high-strength outer shell covering the core.
[0119] like Figure 4 As shown, the energy storage sandwich includes a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell.
[0120] The cement-based electrolyte comprises the following components in parts by mass:
[0121]
[0122] The ultra-high performance concrete shell includes the following components in parts by mass:
[0123]
[0124] In this comparative example, the positive electrode is a vanadium oxide mesh electrode, and the negative electrode is a zinc mesh electrode.
[0125] In this comparative example, the cementitious material includes the following components in mass fractions: 80% silicate cement, 10% fly ash, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically a high early strength polycarboxylic acid water reducer; the modifier is polyacrylamide (weight average molecular weight is 10 million Daltons); the early strength agent includes the following components in mass fractions: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5. The filler includes the following components in mass fractions: 20% silica fume, 72% quartz sand with a particle size of 0.4-1 mm, and 8% quartz powder with a particle size of 5-100 μm.
[0126] The preparation process of the high-strength energy storage floor tile is as follows: first, 70 parts of cementitious material, 0.18 parts of water reducing agent, 5.25 parts of early strength agent and 35 parts of water are placed in a stirring pot and mixed evenly, and then 0.11 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into an energy storage sandwich mold 5 with a high thermal conductivity platform 1 at the bottom (structure as shown in FIG. Figure 1-3 As shown), after standing for 10 seconds, it is placed in a cement standard curing box and cured for 28 days to obtain an energy storage sandwich material B with a directional pore structure. The energy storage sandwich material B is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain an energy storage sandwich material C, i.e., a cement-based electrolyte. The vanadium oxide mesh electrode and the zinc mesh electrode are immersed in liquid nitrogen and frozen for 30 seconds, and then taken out and quickly spliced with the energy storage sandwich material E with a directional pore structure to obtain an assembled energy storage sandwich D.
[0127] 130 parts of Portland cement and 215 parts of filler were poured into a stirring pot and stirred at a speed of 130 r / min for 1 minute. 27 parts of water and 3.15 parts of water reducer were mixed and added to a stirrer and stirred at a speed of 60 r / min for 3 minutes to obtain slurry E. A portion of slurry G was poured into a high-strength shell mold 7 (such as Figure 5 As shown), make the slurry E flush with the base 6 in the high-strength shell mold 7, place the mold on a concrete vibration table and vibrate for 30 seconds, then put the assembled energy storage sandwich D into the base 6 of the high-strength shell mold 7, pour in the remaining slurry E, place the mold on a concrete vibration table and vibrate for 50 seconds, put it into a standard concrete curing box, and after 28 days, high-strength energy storage floor tiles are obtained. The prepared high-strength energy storage floor tiles have a size of 300×300×15mm, and the size of the energy storage sandwich is 260×260×7mm.
[0128] Comparative Example 3
[0129] A high-strength energy storage floor tile comprises an energy storage core and a high-strength outer shell covering the core.
[0130] like Figure 4 As shown, the energy storage sandwich includes a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell.
[0131] The cement-based electrolyte comprises the following components in parts by mass:
[0132]
[0133] The ultra-high performance concrete shell includes the following components in parts by mass:
[0134]
[0135] In this comparative example, the positive electrode is a vanadium oxide sheet electrode, and the negative electrode is a zinc sheet electrode.
[0136] In this comparative example, the cementitious material includes the following components in mass fractions: 80% silicate cement, 10% fly ash, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically a high early strength polycarboxylic acid water reducer; the modifier is polyacrylamide (weight average molecular weight is 10 million Daltons); the early strength agent includes the following components in mass fractions: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5. The filler includes the following components in mass fractions: 20% silica fume, 72% quartz sand with a particle size of 0.4-1 mm, and 8% quartz powder with a particle size of 5-100 μm.
[0137] The preparation process of the high-strength energy storage floor tile is as follows: first, 70 parts of cementitious material, 0.18 parts of water reducer, 5.25 parts of early strength agent and 35 parts of water are placed in a stirring pot and mixed evenly, and then 0.11 parts of modifier are placed in a stirring pot and mixed evenly to obtain slurry A. Slurry A is poured into a mold with a high thermal conductivity platform at the bottom, and after standing for 10 seconds, it is transferred to an ultra-low temperature medium for freeze casting, and frozen for 24 hours until the block is completely solidified to obtain a solidified energy storage sandwich material B. The energy storage sandwich material B is slowly thawed in an environment of 0-4°C for 20 hours to obtain energy storage sandwich material C, and the energy storage sandwich material C is placed in a cement standard curing box and cured for 28 days to obtain an energy storage sandwich material D with a directional pore structure. The energy storage sandwich material D with a directional pore structure is soaked in a 2M zinc sulfate solution for 48 hours, taken out and allowed to stand for 3 hours to obtain an energy storage sandwich material E with a directional pore structure, i.e., a cement-based electrolyte. The vanadium oxide sheet electrode and the zinc sheet electrode are spliced with the energy storage sandwich material E having a directional pore structure to obtain an assembled energy storage sandwich F.
[0138] 130 parts of Portland cement and 215 parts of filler were poured into a stirring pot and stirred at a speed of 130 r / min for 1 minute. 27 parts of water and 3.15 parts of water reducer were mixed and added to a stirrer and stirred at a speed of 60 r / min for 3 minutes to obtain slurry G. A portion of slurry G was poured into a high-strength shell mold 7 (such as Figure 5 As shown), make the slurry G flush with the base 6 in the high-strength shell mold 7, place the mold on a concrete vibration table and vibrate for 30 seconds, then place the assembled energy storage sandwich F on the base 6 of the high-strength shell mold 7, pour in the remaining slurry G, place the mold on a concrete vibration table and vibrate for 50 seconds, put it into a standard concrete curing box, and after 28 days, high-strength energy storage floor tiles are obtained. The prepared high-strength energy storage floor tiles have a size of 300×300×15mm, and the size of the energy storage sandwich is 260×260×7mm.
[0139] Referring to the national standard "Test Method for Cement Mortar Strength (ISO Method)" (GB / T17671-2021), the compression test was carried out on the energy storage floor tiles prepared in the above Examples 1-3 and Comparative Examples 1-3, and the testing instrument was a universal testing machine. The electrochemical impedance spectroscopy was used to study the interface impedance, and the electrolyte ion conductivity and the electrode and electrolyte cross-sectional impedance were obtained by fitting and calculation. At 25°C, 1mA / cm 2 The coulombic efficiency of cement-based zinc batteries was tested after 10,000 cycles at a current density of .
[0140] Table 1 Performance of cement-based zinc batteries prepared in Examples 1-3 and Comparative Examples 1-3
[0141]
[0142] It can be seen from Table 1 that, compared with Comparative Example 2, the ionic conductivity of the cement-based electrolyte with a directional pore structure prepared by freeze casting technology in Examples 1-3 is higher; compared with Comparative Example 1, the energy storage floor tiles prepared by using ultra-high performance concrete as the outer shell in Examples 1-3 have higher compressive strength; compared with Comparative Example 3, the energy storage floor tiles prepared by using a mesh energy storage sandwich mold and mesh electrodes in Examples 1-3 have a smaller interface impedance; compared with Comparative Examples 2 and 3, Examples 1-3 exhibit better stability. The reason is that Comparative Example 2 does not use the freeze casting process, which results in a significant decrease in the ion transmission efficiency inside its material. As for Comparative Example 3, since no mesh electrodes are used, the stability of its contact performance is affected. Therefore, Examples 1-3 effectively improve their overall stability by using freeze casting and mesh electrodes.
[0143] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A high-strength energy storage floor tile, characterized in that: It includes an energy storage core and a high-strength shell covering it.
2. A high-strength energy storage floor tile according to claim 1, characterized in that: The energy storage sandwich includes a cement-based electrolyte and a positive electrode and a negative electrode assembled on opposite sides of the cement-based electrolyte, and the high-strength shell is an ultra-high performance concrete-based shell; The cement-based electrolyte has a directional pore structure with a pore size of 10-20 μm and a porosity of 25-40%; The positive electrode and the negative electrode are mesh electrodes; The length × width of the energy storage sandwich is (250-260) × (250-260) mm, and the vertical height is 5-7 mm. The length × width of the high-strength energy storage floor tile is (290-300) × (290-300) mm, and the vertical height is 13-15 mm. The pores of the directional pore structure are oriented in the same direction as the vertical direction of the cement-based electrolyte, and the positive electrode and the negative electrode are respectively arranged on both sides of the vertical direction of the cement-based electrolyte.
3. A high-strength energy storage floor tile according to claim 2, characterized in that: The cement-based electrolyte comprises the following components in parts by mass: The ultra-high performance concrete-based shell includes the following components in parts by mass:
4. A high-strength energy storage floor tile according to claim 3, characterized in that: The cementitious material is selected from any one or more of silicate cement, fly ash, and silica fume; The water reducer in the cement-based electrolyte and ultra-high performance concrete-based shell components is a polycarboxylate water reducer; The modifier is polyacrylamide; The early strength agent is selected from any one or more of gypsum and water glass; The filler is selected from any one or more of silica fume, quartz sand, and quartz powder.
5. A method for preparing the high-strength energy storage floor tile according to any one of claims 1 to 4, characterized in that: The steps include: S1: Mix the cementitious material, water reducing agent, early strength agent and water, then add the modifier, and mix them to obtain slurry A; S2: Pour slurry A into the energy storage sandwich mold and let it stand; S3: placing the energy storage sandwich mold filled with slurry A on an ultra-low temperature medium for freeze casting to obtain a solidified energy storage sandwich material B; S4: thawing the solidified energy storage sandwich material B to obtain energy storage sandwich material C, and then placing the energy storage sandwich material C in a cement standard curing box for curing for 20-32 days to obtain energy storage sandwich material D with a directional pore structure; S5: immersing the energy storage sandwich material D having a directional pore structure into an electrolyte solution to obtain an energy storage sandwich material E having a directional pore structure, namely a cement-based electrolyte; S6: Immerse the electrode material in a liquid nitrogen solution for cold shrinkage, and then quickly splice the electrode with the energy storage sandwich material E having a directional pore structure to obtain an assembled energy storage sandwich F; S7: Stir the silicate cement and filler in proportion, add the mixed solution of water reducer and water, and stir again to obtain slurry G; S8: Place the energy storage sandwich into a high-strength shell mold, pour in slurry G, make the slurry G surround the energy storage sandwich, and after curing in a standard concrete curing box for 20-32 days, obtain the high-strength energy storage floor tile.
6. The method for preparing a high-strength energy storage floor tile according to claim 5, characterized in that: In step S2, the energy storage sandwich mold comprises a high thermal conductivity platform (1), a grid base (2) arranged on the high thermal conductivity platform (1), a low thermal conductivity frame (3) arranged around the grid base (2), and a low thermal conductivity grid cover (4) arranged on the low thermal conductivity frame (3); in the energy storage sandwich mold, only the high thermal conductivity platform (1) is in contact with the ultra-low temperature medium.
7. The method for preparing a high-strength energy storage floor tile according to claim 5, characterized in that: In step S5, the electrolyte solution is a zinc sulfate solution, and the concentration of the zinc sulfate solution is 1-2M; In step S6, the electrode material is a mesh electrode, the electrode material includes a positive electrode and a negative electrode, the positive electrode is a vanadium oxide mesh electrode, the negative electrode is a zinc mesh electrode, and the electrode material is immersed in a liquid nitrogen solution for shrinkage for 20-40 seconds.
8. The method for preparing a high-strength energy storage floor tile according to claim 5, characterized in that: Step S8 includes the following steps: S8.1: Pour 35-50wt% of slurry G into the high-strength shell mold, and the height of the poured slurry G needs to be flush with the base in the high-strength shell mold; S8.2: Place the assembled energy storage sandwich F on the base in the high-strength shell mold, pour in the remaining slurry G, so that the slurry G surrounds the energy storage sandwich and cure it in a standard concrete curing box for 20-32 days to obtain the high-strength energy storage floor tile.
9. The method for preparing a high-strength energy storage floor tile according to claim 8, characterized in that: In step S8.1, after pouring the 35-50wt% slurry G, the high-strength shell mold needs to be placed on a concrete vibration table and vibrated for 20-40s; In step S8.2, after pouring the remaining slurry G, the high-strength shell mold needs to be placed on a concrete vibration table and vibrated for 40-60 seconds; The entire process of step S8 takes no more than 5 minutes to complete.
10. Application of the high-strength energy storage floor tile according to any one of claims 1 to 4 in the field of building decoration.
Citation Information
Patent Citations
Lithium battery composite electrode pole piece and preparation method and application thereof
CN111933940A
Fabricated high-strength thermal-insulation composite external wall panel and preparation method thereof
CN115613741A
Energy conversion / storage system based on high-conductivity / heat-conductivity ultra-high performance concrete and application of energy conversion / storage system
CN115748350A
Rechargeable cement-based battery and preparation method thereof
CN117577964A
Deep groove type cement-based supercapacitor and preparation method thereof
CN117954235A
Cited By
Energy storage deicing building block brick based on industrial waste
CN121992694A